Factors Affecting Ablation Success After I-131 Radioactive Iodine Therapy in Low and Intermediate Risk Papillary Thyroid Cancer - Goksel, Sibel; Avci, Ugur (Hormone and Metabolic Research, 2023)
The study was to evaluate the effect of radioactive iodine (RAI) treatment application time and clinical, histopathological factors on ablation success in patients with operated papillary thyroid cancer (PTC) in low and intermediate-risk. One hundred sixty-one patients with PTC in the low and intermediate-risk were evaluated. Most patients (89.4%) were in the low-risk, and 10.6% were in the intermediate-risk. When the patients were divided into two groups according to the date of receiving RAI treatment after surgery, those who received early treatment (≤3 months) constituted the majority of the patients (72.7%). Seventeen patients received 1.85 Gigabecquerel (GBq), 119 3.7 GBq, 25 5.55 GBq RAI. Most patients (82%) achieved ablation success after the first RAI treatment. The time interval between surgery and RAI treatment did not affect ablation success. Stimulated Tg level measured on the RAI treatment day was an independent predictive factor for successful ablation (p<0.001). The cut-off value of Tg found to predict ablation failure was 5.86 ng/ml. It was concluded that 5.55 GBq RAI treatment could predict ablation success compared to 1.85 GBq dose (p=0.017). It was concluded that having a T1 tumor may predict treatment success compared to a T2 or T3 tumor (p=0.001, p<0.001, retrospectively). The time interval does not affect ablation success in low and intermediate-risk PTC. The ablation success rate may decrease in patients who receive low-dose RAI and have high Tg levels before treatment. The most crucial factor in achieving ablation success is giving enough doses of RAI to ablate the residual tissue.
Keywords: intermediate risk; low risk; papillary thyroid cancer; radioiodine ablation; successful ablation